Effect of strength training on biomechanical and neuromuscular variables in distance runners: A systematic review and meta-analysis - Trowell, D.; Vicenzino, B.; Saunders, N.; Fox, A.; Bonacci, J. (Sports Medicine, 2020)
Background: Concurrent strength and endurance (CSE) training improves distance running performance more than endurance training alone, but the mechanisms underpinning this phenomenon are unclear. It has been hypothesised that biomechanical or neuromuscular adaptations are responsible for improvements in running performance; however, evidence on this topic has not been synthesised in a review. Objective: To evaluate the effect of CSE training on biomechanical and neuromuscular variables in distance runners. Methods: Seven electronic databases were searched from inception to November 2018 using key terms related to running and strength training. Studies were included if the following criteria were met: (1) population: `distance` or `endurance` runners of any training status; (2) intervention: CSE training; (3) comparator: running-only control group; (4) outcomes: at least one biomechanical or neuromuscular variable; and, (5) study design: randomised and non-randomised comparative training studies. Biomechanical and neuromuscular variables of interest included: (1) kinematic, kinetic or electromyography outcome measures captured during running; (2) lower body muscle force, strength or power outcome measures; and (3) lower body muscle-tendon stiffness outcome measures. Methodological quality and risk of bias for each study were assessed using the PEDro scale. The level of evidence for each variable was categorised according to the quantity and PEDro rating of the included studies. Between-group standardised mean differences (SMD) with 95% confidence intervals (95% CI) were calculated for studies and meta-analyses were performed to identify the pooled effect of CSE training on biomechanical and neuromuscular variables. Results: The search resulted in 1578 potentially relevant articles, of which 25 met the inclusion criteria and were included. There was strong evidence that CSE training significantly increased knee flexion (SMD 0.89 [95% CI 0.48, 1.30], p < 0.001), ankle plantarflexion (SMD 0.74 [95% CI 0.21-1.26], p = 0.006) and squat (SMD 0.63 [95% CI 0.13, 1.12], p = 0.010) strength, but not jump height, more than endurance training alone. Moderate evidence also showed that CSE training significantly increased knee extension strength (SMD 0.69 [95% CI 0.29, 1.09], p < 0.001) more than endurance training alone. There was very limited evidence reporting changes in stride parameters and no studies examined changes in biomechanical and neuromuscular variables during running. Conclusions: Concurrent strength and endurance training improves the force-generating capacity of the ankle plantarflexors, quadriceps, hamstrings and gluteal muscles. These muscles support and propel the centre of mass and accelerate the leg during running, but there is no evidence to suggest these adaptations transfer from strength exercises to running. There is a need for research that investigates changes in biomechanical and neuromuscular variables during running to elucidate the effect of CSE training on run performance in distance runners. Key Points Concurrent strength and endurance training appears to benefit knee flexion, ankle plantarflexion, knee extension and squat strength in distance runners more than endurance training alone. Concurrent strength and endurance training may improve distance running performance by increasing the force-generating capacity in the muscles responsible for centre of mass propulsion and acceleration of the leg during swing. No studies have investigated whether changes in biomechanical and neuromuscular variables following concurrent strength and endurance training transfer to running.